2021
DOI: 10.1007/s40846-021-00608-0
|View full text |Cite
|
Sign up to set email alerts
|

Performance Comparison of the Deep Learning and the Human Endoscopist for Bleeding Peptic Ulcer Disease

Abstract: Purpose Management of peptic ulcer bleeding is clinically challenging. Accurate characterization of the bleeding during endoscopy is key for endoscopic therapy. This study aimed to assess whether a deep learning model can aid in the classification of bleeding peptic ulcer disease. Methods Endoscopic still images of patients (n = 1694) with peptic ulcer bleeding for the last 5 years were retrieved and reviewed. Overall, 2289 images were collected for deep l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 30 publications
(44 reference statements)
2
25
0
Order By: Relevance
“…In an Italian study, Forrest Ia/b lesions showed a high interobserver agreement, whereas Forrest II/III lesions exhibited a low agreement [25]. To explore whether AI is useful for identifying the endoscopic characteristics of hemorrhage during endoscopy, our study [26] initiated the proposal of a DL model that can classify endoscopic images with different bleeding risks according to the Forrest classification and using 2378 still endoscopic images from 1694 patients with PUB (Figure 3). The agreement of the model was moderate to substantial with the senior endoscopist on the To explore whether AI is useful for identifying the endoscopic characteristics of hemorrhage during endoscopy, our study [26] initiated the proposal of a DL model that can classify endoscopic images with different bleeding risks according to the Forrest classification and using 2378 still endoscopic images from 1694 patients with PUB (Figure 3).…”
Section: Application Of Ai During Endoscopymentioning
confidence: 99%
See 1 more Smart Citation
“…In an Italian study, Forrest Ia/b lesions showed a high interobserver agreement, whereas Forrest II/III lesions exhibited a low agreement [25]. To explore whether AI is useful for identifying the endoscopic characteristics of hemorrhage during endoscopy, our study [26] initiated the proposal of a DL model that can classify endoscopic images with different bleeding risks according to the Forrest classification and using 2378 still endoscopic images from 1694 patients with PUB (Figure 3). The agreement of the model was moderate to substantial with the senior endoscopist on the To explore whether AI is useful for identifying the endoscopic characteristics of hemorrhage during endoscopy, our study [26] initiated the proposal of a DL model that can classify endoscopic images with different bleeding risks according to the Forrest classification and using 2378 still endoscopic images from 1694 patients with PUB (Figure 3).…”
Section: Application Of Ai During Endoscopymentioning
confidence: 99%
“…Therefore, the DL model has potential use, particularly in aiding young endoscopists in decision making during emergent endoscopy. To explore whether AI is useful for identifying the endoscopic characteristics of hemorrhage during endoscopy, our study [26] initiated the proposal of a DL model that can classify endoscopic images with different bleeding risks according to the Forrest classification and using 2378 still endoscopic images from 1694 patients with PUB (Figure 3). The agreement of the model was moderate to substantial with the senior endoscopist on the testing dataset.…”
Section: Application Of Ai During Endoscopymentioning
confidence: 99%
“…Until now, data on the efficacy and safety of GLE/PIB in patients with compensated cirrhosis are still limited in the real-world setting [15,16], especially for the Asian population. Thus, this study aimed to evaluate the real-world safety and efficacy of GLE/PIB in patients with compensated cirrhosis from five hospitals in the Changhua Christian Care System [9,17].…”
Section: Introductionmentioning
confidence: 99%
“…With the improvement of endoscopic techniques, small perforations may be successfully sealed with clips intraoperatively. Large perforations may need laparoscopic surgery, with increased complication rates and prolonged hospitalization days [5,13,[19][20][21]. The perforation rate during ESD for SET is reportedly 4-27.2% [9,[22][23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%